The Impact of Reading Aloud on Students’ Pronunciation Awareness to Improve Silent Letters: Perceptions & Recognition - Kustila, Anugerah Wiji; Ardini, Sukma Nur; Adi, Adi Bambang Prabowo Kusumo (JOLLT Journal of Languages and Language Teaching, 2025)
Reading aloud is closely related to students' pronunciation awareness. The study explores the impact of reading aloud on students' pronunciation awareness, focusing on their perceptions and the recognition. Silent letters pose a significant challenge in English pronunciation, often leading to difficulties in understanding and communication. A qualitative design that involved students by practicing the pronunciation of silent letters by reading aloud was employed within nineteen students of the eleventh-grade students at SMK N 2 Semarang using questionnaire and interview focusing on students' ability to correctly pronounce words with silent letters and their overall awareness. The findings revealed that students' pronunciation accuracy and students' awareness who practiced using reading aloud showed a noticeable improvement. The students’ perception of using reading aloud achieved an agreement percentage of 89.5%, indicating that it could improve their silent letter pronunciation. Additionally, it heightened the students' awareness of proper pronunciation and phonetic nuances, contributing to their overall linguistic competence. The second objective referring to the recognition that revealed a mix of positive and negative perceptions, highlighting the complexity of pronunciation strategies in EFL (English as a Foreign Language) education. This research offers valuable insights into how active speaking practices can effectively address specific phonological challenges in language learning.